Gender, sex, and sexuality among contemporary youth - Claster, Patricia Neff; Blair, Sampson Lee (Sociological studies of children and youth, 2017)
Researchers, practitioners, and parents have increasingly become concerned about issues related to sex, gender, and sexuality among children and adolescents. With access to the Internet, young people around the globe can readily obtain virtually any and all information they seek concerning sex and sexuality. In many cultures, the clothing and fashions of children, adolescents, and young adults are increasingly merging, leaving little clear distinction between them, and creating what some consider to be the 'sexualization' of children's and adolescents' clothing. Coinciding with such changes, young people are more openly expressing their own gender identity, often leading to considerable social debate about feminine and masculine identities, and also transgendered identities. This collection provides unique insight into identity formation for contemporary youth and examines the evolving norms concerning sex, gender, and sexuality in the lives of children and adolescents addressing topics including the development of gender identity, sexual behavior among youth, LGBT youth, transgendered youth, parental and peer influences upon the development of gender and gender identity and dating violence.